Reassessing trade barriers with global value chains - Yuko Imura (Bank of Canada, 2019)
This paper provides a systematic, quantitative analysis of the short-run and long-run effects of various trade-restricting policies in the presence of global value chains and multinational production. Using a two-country dynamic stochastic general equilibrium model with endogenous firm entry and exit in both exporting and multinational production, I compare the effects of (i) tariffs on final-good imports, (ii) tariffs on intermediate-input imports, and (iii) barriers to accessing foreign markets. I show that, in the long run, all three policies lead to a recession in both countries, but the relative effects on the GDP of the two countries vary across policies. At the firm level, less productive exporters exit from the destination market while the most productive few find it profitable to locate production in the foreign country as multinationals, thereby partially recovering the loss from exporting. In the short run, the dynamics differ across policies and from their long-run outcomes. Final-good tariffs and market-access barriers lead to a temporary production boom in the policyimposing country, while intermediate-input tariffs result in an immediate recession in both countries. The latter also discourages multinational operation over the short run when the input tariffs dominate the declining costs of labor and capital.
Keywords: F13; F41; F12; 330; Bank topics; Firm dynamics; International topics; Trade integration; Business fluctuations and cycles